Exonuclease III-assisted multiple cycle amplification for the sensitive detection of DNA with zero background signal. Issue 22 (3rd October 2018) - Liu, Wen-Jing; Xu, Qinfeng; Ma, Fei; Li, Chen-Chen; Zhang, Chun-Yang
Abstract : We demonstrate the development of Exo III-assisted multiple cycle amplification for the sensitive detection of DNA with zero background signal. Abstract : Detection of low-abundant DNA is essential for disease diagnosis and treatment. DNA polymerase-based amplification is frequently used due to its excellent sensitivity, but it suffers from time-consuming and labour-intensive procedures, complex template/primer design, and inherent nonspecific amplification. Alternatively, Exonuclease III (Exo III)-assisted target recycling provides a new approach for DNA assay because of its simplicity and general applicability, but it suffers from high background signal due to the nonspecific Exo III digestion and poor sensitivity due to single cycle signal amplification. Herein, we demonstrate the development of Exo III-assisted multiple cycle amplification (exonuclease chain reaction) for the sensitive detection of DNA with zero background signal. The binding of single-stranded DNA binding protein (SSB) to the hairpin probes can protect them from nonspecific digestion by Exo III, resulting in near zero background signal. The presence of the target DNA initiates the Exo III-triggered multiple cycle amplification, enabling the achievement of high sensitivity with a detection limit of 3 fM and excellent selectivity with single base mismatch discrimination capability, holding great potential in disease diagnosis and biomedical research.